P227 Molecular and functional characterisation of distinct resident and migratory skin fibroblast populations in systemic sclerosis. (23rd April 2022) - Clark, Kristina E. N; Cole, Alice; Xu, Shiwen; Ong, Voon H; Buckley, Christopher D; Denton, Christopher P
Abstract: Background/Aims: Modern single-cell analysis has confirmed functional heterogeneity amongst fibroblast populations within normal and diseased skin. To better understand differences between fibroblast subpopulations, we have developed a novel technique to selectively isolate "migratory" fibroblasts, and non-migratory "resident" fibroblasts from heathy control (HC) and systemic sclerosis (SSc) skin and used functional assays of fibrotic potential, and gene expression to compare these novel fibroblasts populations. Methods: Forearm skin punch biopsies were collected from dcSSc (n = 3), and HC skin (n = 3). Migratory fibroblasts were isolated by standard explant culture. The remaining biopsy fragments then underwent collagenase digestion to yield a population of resident fibroblasts. These populations were expanded and used at passage 3-6. Functional characterisation included 3-D collagen gel contraction, and migratory scratch-wound assays. Expression of pro-collagen I, CTGF and alphaSMA was compared by western blot. Bulk RNAseq on each fibroblast population was performed. Statistical analysis was carried out using Rsoftware "tidyverse". Significant differences in gene expression were those with a fold change of ≥ 1.5, and adjusted p-value (FDR) of < 0.05. Results: SSc fibroblasts showed a hallmark fibrotic phenotype with increased gel contraction, faster migration, and overexpression of Col1, CTGF and alphaSMA compared with HC. Conversely, resident fibroblasts showed reduced contraction, migration, and reduced secretion of alphaSMA compared to migratory fibroblasts in both SSc and HCs. RNAseq confirmed 1483 significantly differentially expressed genes between SSc resident and migratory fibroblasts, whereas no genes were significantly differentially expressed between HC resident and migratory fibroblasts. To further understand disease-related differences between the two fibroblast populations, we compared gene expression between SSc and HC migratory fibroblasts, and resident fibroblasts. 644 genes were upregulated in the migratory fibroblasts of SSc compared to HC (including ACTA2, C1QTNF3). 914 genes were upregulated in SSc resident fibroblasts compared to HC (including IL6, CCL2). Of these 375 genes were upregulated in both SSc fibroblast populations compared to HC (Table 1 ) including IL11 and COMP. Conclusion: There are clear functional and transcriptional differences between migratory and resident fibroblasts, which is more marked in SSc compared to HC. Further work is required to understand their role in SSc pathogenesis and contribution to disease phenotype that may facilitate a more targeted approach to treatment Disclosure: K.E.N. Clark: None. A. Cole: None. S. Xu: None. V.H. Ong: None. C.D. Buckley: Corporate appointments; founder of Mestag Therapeutics. C.P. Denton: None.